Assessment of Physicochemical, Heavy Metals and Microbial Parameters in Leachate and Groundwater around Solid Waste Dumpsites at Onne, Rivers State, Nigeria - T. O. Olagbemiro; I. K. E. Ekweozor; A. P. Ugbomeh; D. N. Ogbonna; K. N. O. Bob-Manuel; F. A. Green; B. H. Nwibani (Journal of Applied Sciences and Environmental Management)
The study assessed groundwater contamination from dumpsite leachate in Onne, Nigeria, over 12 months (May 2022–May 2023). Physicochemical (pH, EC, DO, BOD, TDS, turbidity, sulphate, phosphate, nitrate), heavy metals (Cr, Cd, Pb, Hg, Fe, Cu), and microbial (faecal and total coliform) parameters were analyzed in leachate and groundwater samples using standard methods. Statistical analysis (ANOVA, Tukey's HSD post-hoc, Pearson correlation) evaluated spatial variations and relationships between leachate and groundwater characteristics. Results showed significant contamination, with EC (232.3 ± 25.9 µs/cm), sulphate (3.77 ± 0.38 mg/L), phosphate (6.14 ± 0.36 mg/L), nitrate (1.19 ± 0.25 mg/L), Fe (0.32 ± 0.12 mg/L), Pb (0.02 ± 0.03 mg/L), and Hg (0.01 ± 0 mg/L) in groundwater samples, some exceeding WHO/NSDWQ limits. Leachate contained significantly higher levels of heavy metals, particularly Fe (77.4 ± 16.3 mg/L), Cu (23.1 ± 4.73 mg/L), and Cr (1.23 ± 0.4 mg/L), suggesting potential leachate migration influencing groundwater quality. Microbial counts (<2 MPN/g) remained within acceptable limits, with no significant variation. The analysis revealed significant spatial variations in the physicochemical, heavy metal, and microbial parameters across the dumpsites. The following recommendations are made; implement waste segregation and recycling programs at the source to reduce the amount of waste reaching the dumpsites and develop and implement leachate treatment systems to prevent contamination of groundwater and soil.